Investigating Successive Interference Cancellation in MIMO Relay Network - Toding, Apriana; Rong, Yue (IEEE, 2011)
In this paper, we study the zero-forcing (ZF) and minimum mean-squared error (MMSE) algorithms for a multiple-input multiple-output (MIMO) relay network and compare their performance in terms of bit-error-rate (BER). In particular, we investigate their performance with and without using the successive interference cancellation (SIC) at the receiver. Our results demonstrate that the system performance can be significantly improved by using the SIC technique.